On the Relationship between Gross Domestic Product and Energy: A Critical Comment - Lianos, Theodore P.; Pseiridis, Anastasia; Tsounis, Nicholas (International Journal of Energy Economics and Policy, 2020)
GNP and energy. The obvious interest in this relationship is a result of the global interest in reducing the use of energy without impairment of economic growth. Most studies do not have an economic model underlying the statistical models. In the absence of an economic model supporting the estimable equations, the statistical results can be interpreted arbitrarily or they may not have an interpretation that can be theoretically supported. In this paper we attempt to do four things. First, we briefly present the four hypotheses that have been formulated to express the energy-GDP relationship. Second, we argue that the relationship between GDP and energy, as is formulated in two of the hypotheses (the growth hypothesis and the feedback hypothesis), and as is examined in part of this literature, suffers from misspecification, because a decisive factor for the energy market is missing. Third, we use basic economic theory to show how GDP and energy are related on the basis of production theory and derived demand for factors of production, and, fourth, we conclude by suggesting which of the four hypotheses can serve as a meaningful approximation of the relationship. Keywords: GDP-energy nexus, Conservation hypothesis, Growth hypothesis, Feedback hypothesis, Neutrality hypothesis JEL Classifications: Q41, Q43 DOI: https://doi.org/10.32479/ijeep.8418